2018
DOI: 10.1039/c8ra08757a
|View full text |Cite
|
Sign up to set email alerts
|

Production of cyclopentanone from furfural over Ru/C with Al11.6PO23.7 and application in the synthesis of diesel range alkanes

Abstract: Cyclopentanone as the substrate for the synthesis of jet fuel range cyclic alkanes can be prepared through the cyclopentenone route under mild conditions and catalyzed by Ru/C with Al11.6PO23.7 from furfural.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 60 publications
1
29
0
Order By: Relevance
“…These re-sults indicated that, the first step reaction would be the hydrogenation of C=O bond of FFald to produce FFalc. During the reaction, FFalc is converted via Piancatelli rearrangement into CPO whereas the 4-hydroxy-2cyclopentenone (4-HCP) is the intermediate product [10,34]. However, once the THFalc was formed, the formation of CPO or CPL will be constant as indicated in Figure 4 due to the activation and hydrogenolysis of hydrofuran ring of THFalc required a specific active site, such as strong acid site or multicenter metal catalysts [5,35].…”
Section: Kinetic Profilesmentioning
confidence: 99%
See 1 more Smart Citation
“…These re-sults indicated that, the first step reaction would be the hydrogenation of C=O bond of FFald to produce FFalc. During the reaction, FFalc is converted via Piancatelli rearrangement into CPO whereas the 4-hydroxy-2cyclopentenone (4-HCP) is the intermediate product [10,34]. However, once the THFalc was formed, the formation of CPO or CPL will be constant as indicated in Figure 4 due to the activation and hydrogenolysis of hydrofuran ring of THFalc required a specific active site, such as strong acid site or multicenter metal catalysts [5,35].…”
Section: Kinetic Profilesmentioning
confidence: 99%
“…Recently, cyclopentanone (CPO) and cyclopentanol (CPL), versatile chemical intermediates that containing five-membered alicyclic rings, can be obtained via combined-step of hydrogenation and rearrangement of biomassderived furfural in aqueous media using carbon supported platinum or palladium-based catalysts [7][8][9]. CPO and CPL can be utilized as precursor of medicines, rubber, fuel energy, and materials CPO is also used in the fragrance and perfume industry as there are the major ingredients of jasmine family [10][11][12]. Traditionally, the synthesis of CPO involves catalytic vapor-phase cyclization of 1,6-hexandiols or ester of adipic acid with yields of 53% and 22%, respectively [13][14].…”
Section: Introductionmentioning
confidence: 99%
“…CPO is produced by the rearrangement of FAL. Many researchers have investigated the hydrogenation of furfural to CPO, which is generally performed over Co/ZrO 2 -La 2 O 3 , CuZnAl, Cu/CNT, Pd/C, and Ru/C catalysts; the reaction pathways are shown in Figure 1 [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…In an aqueous solution, high selectivity of furfural conversion into cyclopentanone was achieved at 160 °C (70%) > 140 °C (3%) > 120 °C (0%); however, too high temperature (180 °C) also led to 0% selectivity of cyclopentanone due to further conversion of cyclopentanone into cyclopentanol under a moderate hydrogen pressure (2−4 MPa). 71 Co/Al 2 O 3 produced substantially high amount of acids, which was not favorable for bio-oil upgrading. The presence of Mo in bimetallic CoMo/Al 2 O 3 and NiMo/ Al 2 O 3 catalysts gave significantly higher aromatic ketone composition in bio-oil, which was also satisfactory due to a higher HHV and C/O ratio.…”
Section: Resultsmentioning
confidence: 95%
“…Moreover, it was reported that the solvent and temperature considerably influenced the selectivity of the hydrogenation product of furfural. In an aqueous solution, high selectivity of furfural conversion into cyclopentanone was achieved at 160 °C (70%) > 140 °C (3%) > 120 °C (0%); however, too high temperature (180 °C) also led to 0% selectivity of cyclopentanone due to further conversion of cyclopentanone into cyclopentanol under a moderate hydrogen pressure (2–4 MPa) . Co/Al 2 O 3 produced substantially high amount of acids, which was not favorable for bio-oil upgrading.…”
Section: Resultsmentioning
confidence: 98%